Bounded solutions of fourth-order nonlinear elliptic equations with convection terms. Issue 12 (10th September 2021) - Cirmi, G. R.; D'Asero, S.
ABSTRACT: We study a Dirichlet problem associated to a nonlinear fourth-order equation with a convective lower order term and with coefficients of principal part satisfying a strengthened coercivity condition. We obtain the existence of a weak solution and its Hölder's continuity.